(3cJGH aj GdJaSjQs
(3ChdgG (B:s
(3Chd GdehLhO eg bhdg (B: (3jchf jbJdhf dGehVY dgG ef GdEYQGH heKdg ai GdUdI bhdg heGJdc Hjejfc jG ehSi Ci heG GdJi Hjejfc s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3hbGJdhG ai SHjd Gddg hbJdhG ajgG dGcaQf Yfge SjFGJge eYfi dGeMhgG Yfge hdGJaVdf Ydjge HYahi heZaQJi hQMeJi hgPG jOd Ydi Cf ESbGW GdYbGH JaVd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs